Seven prostate cancer susceptibility loci identified by a multi-stage genome-wide association study - Kote-Jarai, Z; Olama, A; Giles, G; Severi, G; Schleutker, J; Weischer, M; Campa, D; Riboli, E; Key, T; Gronberg, H; Hunter, D; Kraft, P; et al. (2011)
Prostate cancer (PrCa) is the most frequently diagnosed male cancer in developed countries. We conducted a multi-stage genome-wide association study for PrCa and previously reported the results of the first two stages, which identified 16 PrCa susceptibility loci. We report here the results of stage 3, in which we evaluated 1,536 SNPs in 4,574 individuals with prostate cancer (cases) and 4,164 controls. We followed up ten new association signals through genotyping in 51,311 samples in 30 studies from the Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome (PRACTICAL) consortium. In addition to replicating previously reported loci, we identified seven new prostate cancer susceptibility loci on chromosomes 2p11, 3q23, 3q26, 5p12, 6p21, 12q13 and Xq12 (P = 4.0 × 10-8 to P = 2.7 × 10-24). We also identified a SNP in TERT more strongly associated with PrCa than that previously reported. More than 40 PrCa susceptibility loci, explaining 425% of the familial risk in this disease, have now been identified. © 2011 Nature America, Inc. All rights reserved.